The Transcription Factor TFEB Links mTORC1 Signaling to Transcriptional Control of Lysosome Homeostasis - Roczniak-Ferguson, Agnes (2012)
Lysosomes are the major cellular site for clearance of defective organelles and digestion of internalized material. Demand on lysosomal capacity varies greatly, but the mechanisms that adjust lysosomal function to maintain cellular homeostasis are unknown. In this study, we identify an interaction between mTOR and the TFEB transcription factor on the surface of lysosomes that allows mTOR to transduce signals arising from changes in lysosomal status to TFEB and thus control the ability of TFEB to enter the nucleus. This occurs via regulation of the serine 211 phosphorylation-dependent binding of 14-3-3 proteins to TFEB. These results identify TFEB as a novel target of mTOR that couples the transcriptional regulation of genes encoding proteins of autophagosomes and lysosomes to cellular need. We further present evidence that the closely related MITF and TFE3 transcription factors are regulated in a similar manner, thus broadening the range of physiological contexts under which such regulation may prove important.